Kiai Dan Pejabat Publik: Study Analisis Peran Ganda Kiai Mujib Imron Dalam Mengembangkan Lembaga Pendidikan Berbasis Pesantren Di Pesantren Al-Yasini Pasuruan - Laila, Itsna Noor (Jurnal Keislaman, 2024)
This research aims to determine the progress of K.H Mujib Imron in developing Islamic boarding school-based educational institutions at the Al-Yasini Pasuruan Islamic boarding school. The problem in this research is the progress of Kiai Mujib Imron as an Islamic boarding school leader and as a public official in developing Islamic boarding school-based educational institutions at the Al-Yasini Pasuruan Islamic boarding school. The research approach used is descriptive qualitative research. The research uses two data sources, namely, primary and secondary. Observation, interview and documentation techniques were used to collect data. The data analysis procedure goes through the stages of data reduction, data display and drawing conclusions. The results of the study show that K.H Mujib Imron's dual role as a kiai and as Deputy Regent of Pasuruan runs well and is in synergy with each other. This is shown by his istiqomahan in carrying out religious activities at the Islamic boarding school, such as reciting the books Ta'lim Muta'alim and Fatkhul Qorib as well as the books Shohih Bukhori and Tafsir Jalalain. Apart from that, two strategic steps were taken, namely in developing educational institutions, namely; 1) internal strategy, namely by motivating every head of educational institution to innovate in implementing an integrated curriculum that is competitive in accordance with current developments in the era of modernity, without neglecting religious education; 2) external strategy, namely by introducing the Al-Yasini educational institution more widely , both at regional level and abroad.